A STUDYA BOUT RISK AND RETURN ON AUTOMOBILE INDUSTRIES - D.BHASKAR, G.R.SRINIVAS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Automobile Industry could be a image of technical marvel by humans. Automobile industry is taken into account to be the quickest growing sectors in any developing and even in a developed country. The risk and return analysis connected with any trade reveals the details attached to the actual industry.. While making the decisions regarding investment and financing, one seeks to achieve the right stability between risk and return, in order to improve the importance of the firm. This study reported a statistical significant relationship between risk and return.The study is undertaken with the main objective of determining the risk and return profile of selected automobile industries. In this article risk and return of Ashok Leyland, Bajaj Auto, and Eicher Motor are analyzed using statistical tools like mean,variance,standard deviation,beta and t-test.Finally, the study proves there's a relation between risk and return of the most effective company among the selected company